The Repayment Capacity of MSME on Micro-Credit Risk through impact analysis of DPK, NPL, and DH level; Case from BRI Kunir branch in Blitar - Kezia Marmina Kentas (Publikasi Indonesia, 2025)
This research examines factors influencing microcredit repayment capacity, focusing on the impacts of DPK (Dalam Pertimbangan Khusus), NPL (Non-Performing Loan), and DH (Daftar Hitam) levels for Kupedes and KUR loans at Bank Rakyat Indonesia's Kunir branch in Blitar. It highlights the role of MSMEs in economic growth and job creation while noting challenges like limited access to finance. Key factors affecting repayment include financial conditions, debt-to-income ratios, and borrower characteristics. Using multinomial logistic regression, the study analyzes the relationship between these variables and repayment performance. Preliminary findings reveal that loan monitoring significantly enhances repayment, reducing default risk by increasing borrower awareness. In contrast, loan size and repayment duration have minimal impact, while collateral negatively affects repayment timeliness, as borrowers may rely on it as a fallback. The study underscores the importance of supervision to maintain repayment stability and suggests that banks could improve oversight, especially for collateralized loans, to minimize bad debts. Insights from this research can aid banks in refining risk management and inform borrowers about factors contributing to repayment challenges. This study focuses on the Kunir area, analyzing data from August 2023 to August 2024, offering a targeted view of microcredit dynamics in Indonesia.